2017
DOI: 10.1016/j.neulet.2017.08.040
|View full text |Cite
|
Sign up to set email alerts
|

The GBA variant E326K is associated with Parkinson's disease and explains a genome-wide association signal

Abstract: Objective: Coding variants in the GBA gene have been identified as the numerically most important genetic risk factors for Parkinson's disease (PD). In addition, genomewide association studies (GWAS) have identified associations with PD in the SYT11-GBA region on chromosome 1q22, but the relationship to GBA coding variants have remained unclear. The aim of this study was to sequence the complete GBA gene in a clinical cohort and to investigate whether coding variants within the GBA gene may be driving reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…Further, we have shown that a previously reported GWAS signal at this locus can be largely explained by protein coding variability within GBA . These data are consistent with p.E365K being the functional effector allele underlying the original GWA locus (GBA‐SYT11 locus), as suggested previously . The results from this current study suggest that efforts directed at replacing or augmenting glucocerebrosidase activity already under way for PD may have wider‐ranging applicability than just for individuals with GD‐associated mutations in glucocerebrosidase.…”
Section: Gba Variant Frequencies In Cases and Controlssupporting
confidence: 91%
“…Further, we have shown that a previously reported GWAS signal at this locus can be largely explained by protein coding variability within GBA . These data are consistent with p.E365K being the functional effector allele underlying the original GWA locus (GBA‐SYT11 locus), as suggested previously . The results from this current study suggest that efforts directed at replacing or augmenting glucocerebrosidase activity already under way for PD may have wider‐ranging applicability than just for individuals with GD‐associated mutations in glucocerebrosidase.…”
Section: Gba Variant Frequencies In Cases and Controlssupporting
confidence: 91%
“…For example, the identification of TREM2 mutations in a handful of patients diagnosed with Alzheimer's disease highlighted the role of microglia and inflammation in that form of neurodegenerative disease and paved the way for innovative approaches to therapy (33). The discovery of GBA mutations had a similar impact on Parkinson's disease research (34).…”
Section: Discussionmentioning
confidence: 98%
“…169,170 This might be because of a differential localization of α-syn pathology, primarily involving oligodendrocytes in MSA, as opposed to neurons in PD and DLB. Third, a number of GBA1 variants not associated with GD have been described in patients with PD 80,171,172 and DLB. 64 Finally, a substantial proportion of GBA1 mutations identified in DLB patients are "mild" variants rather than expected "severe" mutations.…”
Section: Concluding Remarks and Open Questionsmentioning
confidence: 99%